Impact of Delayed Presentation on Outcomes of Adult Emergency Abdominal Surgery - Muhammad Javed Khan, Asif Imran, Asfandyar Khan, Muhammad Mubassir, Sajjad Hussain, Zarka Sarwar, Huma Shafi, Tanzeela Nawaz, Rabia Jadoon (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Delayed presentation in emergency abdominal surgery is a clinically important exposure because acute abdominal pathology may progress from localized inflammation or obstruction to perforation, gangrene, contamination, sepsis and organ dysfunction. Emergency abdominal surgery has a substantial morbidity burden, and outcomes are strongly influenced by baseline physiological risk, operative severity and access to timely surgical care2,3. Objective: To determine the association between delayed presentation, defined as hospital presentation more than 48 hours after symptom onset, and 30-day postoperative outcomes in adult patients undergoing emergency abdominal surgery. Material and Methods: This prospective observational study was conducted in the Department of General Surgery, Mardan Medical Complex, Mardan, Pakistan, from July 2023 to September 2023. Adults aged 18 years or above undergoing emergency abdominal surgery were classified as early presenters within 48 hours or delayed presenters after 48 hours. The primary outcome was 30-day postoperative morbidity. Secondary outcomes included surgical-site infection, ICU admission, length of hospital stay, reoperation and mortality. Group comparisons and multivariable logistic regression were performed. Results: A total of 150 patients were included, comprising 64 early presenters and 86 delayed presenters. Delayed presentation was associated with older age, higher diabetes burden, higher ASA III/IV status and more rural residence. Delayed presenters had higher perforation, gangrene, contaminated or dirty wound classification and open surgery. Morbidity, surgical-site infection, ICU admission and hospital stay were significantly higher in delayed presenters. Delayed presentation remained independently associated with morbidity with adjusted OR 2.38, 95% CI 1.14-4.96, p=0.021. Conclusion: Presentation after 48 hours was associated with advanced operative pathology and worse short-term postoperative outcomes. Early referral, community awareness, emergency triage strengthening and protocol-based emergency surgery pathways may reduce preventable morbidity. Keywords: delayed presentation; emergency abdominal surgery; acute abdomen; surgical morbidity; surgical-site infection; postoperative outcomes.